Limited utilization of extracted dissolved organic matter by prokaryotic communities from the subtropical North Atlantic - Bercovici, Sarah K.; Arroyo, Mar C.; De Corte, Daniele; Yokokawa, Taichi; Hansell, Dennis A.; Arroyo, Mar C.; 2 Department of Ocean Sciences Rosenstiel School of Marine and Atmospheric Science, University of Miami Miami Florida USA; De Corte, Daniele; 1 Institute for Chemistry and Biology of the Marine Environment, Carl Von Ossietzky University of Oldenburg Oldenburg Germany; Yokokawa, Taichi; 4 Institute for Extra‐cutting‐edge Science and Technology Avant‐garde Research (X‐star), Japan Agency for Marine‐Earth Science and Technology Yokosuka Japan; Hansell, Dennis A.; 2 Department of Ocean Sciences Rosenstiel School of Marine and Atmospheric Science, University of Miami Miami Florida USA (Limnology and Oceanography, 2021)
The ocean contains a large reservoir of dissolved organic matter (DOM) that persists for millennia. Both the very dilute concentrations of individual DOM molecules and intrinsic recalcitrance to microbial decay imparted by molecular structure are suggested mechanisms for this long residence time. Here, we report an experiment comparing the responses of surface and deep prokaryotes to DOM isolated and enriched by solid‐phase extraction from surface and deep waters of the subtropical North Atlantic Ocean. Extracts from both depths were qualitatively characterized as biologically recalcitrant given their similarly high C : N ratios of 26. Surface prokaryotes measurably drew down extracted dissolved organic carbon (DOC) concentrations, but the drawdown was only 4% of the initial enriched DOC concentration regardless of enrichment level or depth. Deep microbes, in contrast, did not cause observable changes in DOC concentrations. Surface and deep prokaryotes had similar temperature‐normalized growth responses to extracts from each depth. Biological indicators (e.g., kinetics) suggest that prokaryotes were less efficient at catalyzing surface than deep DOM (catalytic efficiencies of 0.003–0.005 vs. 0.02–0.03 h−1, respectively). These values indicate qualitative differences in extracted DOM from the two depths, perhaps suggesting a variable nature of the refractory DOC depending on depth. Moreover, only a small portion of the extracted DOM was biologically utilizable, regardless of concentration factor or depth, and essentially only a small fraction of it was incorporated into biomass. Microbial selection against substrates that meet modest energy but no growth demands may be a factor contributing to the long‐term stability of marine DOM.